On the Kelvin Transformation in Finite Difference Implementations - Gold, Gerald (Electronics, 2020)
Finite difference operators were applied on a Delaunay mesh. This way it is possible to discretize a radial boundary that is used to perform a Kelvin mapping of an additional outer domain to virtually extend the computation domain to infinity. With an example two-wire problem, the performance of this approach is shown in comparison with a conventional calculation domain and with the analytical solution, respectively. The presented implementation delivers a more precise approximation to the real values and at the same time requires a smaller system of equations—i.e., allows for faster computation
Keywords: Delaunay mesh; FEM mesh; finite differences; infinite differences; Kelvin mapping; Kelvin transformation; open boundary; unbounded grid